Autologous Platelet-Rich Plasma Enhances the Healing of Large Cutaneous Wounds in Dogs - Iacopetti, Ilaria; Patruno, Marco; Melotti, Luca; Martinello, Tiziana; Bedin, Silvia; Badon, Tamara; Righetto, Edoardo Maria; Perazzi, Anna (Frontiers in Veterinary Science, 2020)
Platelet-rich plasma (PRP) is known to play a crucial role in skin wound healing, in both Human and Veterinary Medicine. Remarkably, until now, no studies have reported PRP treatment in subacute full-thickness skin wounds of the dog. The aim of this study was to evaluate the effects of two consecutive applications of autologous PRP, with the second application after 15 days, in 6 dogs showing large subacute skin wounds. The percentage of contraction, re-epithelialization and healing in all treated patients indicated that no complications or side effects, associated with consecutive PRP treatments, occurred in any patient and all wounds achieved complete closure and re-epithelialization. Our results suggest a positive effect of repeated autologous topical PRP treatments in large cutaneous subacute wounds of different aetiology. Therefore, this PRP treatment could represent a simple, cost-effective and valid alternative to promote healing processes in subacute large wounds cases in dogs.